Correlation of neuroimaging findings and outcome in West syndrome - Manandhar, Bina Prajapati; K. C., Divya; Khatun, Najala (International Journal of Contemporary Pediatrics, 2022)
Background: West syndrome (WS), an infantile epileptic encephalopathy which occurs in clusters with developmental regression and hypsarrhythmia. The classification refers to genetic, structural and metabolic cause. Neuroimaging can help to identify various lesion in the brain leading to West syndrome and outcomes can be measured in form of seizure control and neurodevelopmental improvement. We aimed to study the correlation of neuroimaging in West syndrome with the outcomes. Methods: This was a retrospective cross-sectional study done among patients who presented to International friendship children’s hospital. All the cases diagnosed with WS and between 4 months to 5 years of age according to ILAE (International league against epilepsy) were included in this study. The study duration was three years. Fisher’s exact test was used to see correlation of underlying neuroimaging findings with outcome in children with West syndrome. Results: Of 37 children diagnosed with WS, 65% were male with a mean age of presentation 17±7 months and mean age of onset of seizure 5±1 months. Thirty patients had regular follow up and neurodevelopmental outcome could be determined. There was no significant relation between neuroimaging finding and neurodevelopmental outcome along with seizure remission (p>0.05). Improvement in developmental milestones was seen in 17 patients (56.6%) and 1 patient (3.3%) had normal milestone as per age. Conclusions: Neuroimaging is an important diagnostic tool to determine etiology of WS but it’s not the sole component to predict the neurodevelopmental outcome and seizure remission.